Hydroponic Vegetables by Utilizing Beverage Plastic Bottle Waste - Cut Novrita Rizki; Fitriyasni Fitriyasni; Manja Manja; Khaira Ulfi; Mainidar Mainidar (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: The interest of Gampong Baro residents in farming, the limited space for living , the abundance of plastic bottle waste from beverages, and the lack of knowledge among Gampong Baro residents regarding the processing of plastic bottle waste, have turned plastic beverage bottles into mere waste without functional value. The existence of this community service is expected to make the residents of Gampong Baro realize that the accumulated plastic bottle waste will be difficult to decompose in the soil and will have negative health impact if burned. Plastic bottle waste has highly diverse functions if we understand to process it. The purpose of this community service is to provide counseling to Gampong Baro residents on how to utilize plastic bottle waste, one of which is to use it as a media for hydroponic vegetable cultivation. The result of this community service is healthy vegetables grown hydroponically using plastic bottle waste. The purpose of this community service is to reduce plastic bottle waste, enable gardening as a hobby despite limited space. The method used in this community service is the wick system, which is one of the hydroponic methods. The importance of the results of this community service is to inform the residents of Gampong Baro that plastic bottle waste can be utilized and has functions that can yield healthy vegetables, thereby enhancing the economic value of Gampong Baro residents. Keywords: waste; hydroponic; vagetable; gampong baro; plastic bottle.